G329(P) Incidence of amphotericin-induced acute kidney injury in a paediatric population: a systematic review. (25th October 2020) - Mistry, D; Oni, L; McWilliam, SJ
Abstract : Aims: The aim of this project was to perform a systematic literature review to determine the incidence of Amphotericin-induced Acute Kidney Injury (AKI) in the paediatric population. Methods: A systematic review was performed to obtain articles until October 2018 using Scopus and Medline, with additional articles obtained using the bibliographies from selected studies. Studies were chosen if they included an intervention of Amphotericin with monitoring of renal function and a declaration of how AKI would be defined. All types of studies were considered and those retrievable in full text and English were included. Results: Of sixty-three articles identified, seventeen were available in full text. A further ten studies were rejected due to not mentioning dose, duration or outcomes. The remaining seven studies totalled 279 patients aging between 0–15 years. The ratio of boys to girls was 50:50 (demographic data reported in only 4 of 7 studies). Of the seven studies none were randomised controlled trials. Visceral Leishmaniasis was the indication for treatment with liposomal Amphotericin in 6 of the 7 studies. The dose of Amphotericin ranged from 15–30 mg/kg and a duration of 2 – 21 days. The total incidence of AKI was found to be 1%, with the pRIFLE criteria being the most commonly used method of defining AKI, however many of the studies did not explicitly define AKI in their outcome criteria, leading to low identification rates. The optimal dose range is 3–4 mg/kg for a regime of 5-day treatment followed by a further dose on day 10. Additional outcomes included risk factors for AKI with underlying infection being the most consistent. Conclusion: This systematic review found an incidence of Amphotericin-induced AKI in a paediatric population of 1%. Comparatively, adults show an incidence rate of around 50%, suggesting large differences between the two cohorts. There were limitations to this study, mainly due to the lack of standardisation in the definition of drug-induced AKI in children across the studies. Improved reporting of Amphotericin-induced AKI, using standardised AKI definitions, is required to confirm the true incidence in children.